TEKNIK SHADOWING MENINGKATKAN KEMAMPUAN MAHASISWA BERBICARA BAHASA INGGRIS - I Gede Neil Prajamukti Wardhana (SPHOTA: Jurnal Linguistik dan Sastra, 2020)
ABSTRACT The ability to English speaking needs to understand by students in the level of university to face the global challenge nowadays. This research applied the ability English speaking student by shadowing technique. This research has been researched by researcher before in listening and speaking. The different of this research is the research before made the student group as a subject research however on the contrary of this research analyzing the student as individual to look the implementation English speaking and fluency by shadowing technique. This research was descriptive analysis that finding English speaking and difficult words to speak in the English text material. The sample data of student was the student from English study program Dhyana Pura University in the 3rd semester by the year of academic 2016/2017. The method of this research in the collecting data was descriptive analysis method also the technique of collecting data by the process of English speaking teaching and documentation. The result of this research was 11 from 13 students English study program in the 3rd semester by the year of academic 2016/2017 was fluent to understand English speaking and the rest of 2 students had incorrectly to speak in English was the word caught – [’kɔ:t]. Based on this research, need a concern to all lecturers or tutors to teach English speaking to students and one of them by using the shadowing technique. Keywords: Shadowing, Speaking, Individual, Word